Molecular surveillance of hepatitis E virus in wastewater in Yaoundé, Cameroon - Dowbiss Meta-Djomsi; Marie Atsama-Amougou; Modeste Romuald Ngamaleu; Celestin Godwe; Martin Maidadi-Foudi; Marcel Tongo; Joseph Fokam; Charles Kouanfack; Ahidjo Ayouba (PLoS ONE, 2025)
Background Hepatitis E virus (HEV) is a zoonotic pathogen mainly transmitted through contaminated food or water in sub-Saharan countries, highlighting the need for environmental surveillance. This study aimed to assess the burden and molecular characterization of HEV in environmental wastewater. Method A community-based surveillance was conducted in Yaoundé, Cameroon, using untreated wastewater samples collected monthly from January to December 2023 from hospitals, residential sewage systems, markets, and plant watering points. Molecular phylogeny was performed on sequences from the Open Reading Frame 1 region. Results HEV was detected in 26.4% (19/72) of all sites, with prevalence ranging from 8.3% (1/12) in hospitals to 41.7% (5/12) in residential areas (p = 0.0022). Of the 19 positives, HEV detection was highest in specific residential areas (26.3%) and plant watering points (15.8%). Detection rates were significantly higher during the short dry season (36.8%) and long dry season (31.6%) compared to the short-wet season (21.05%) and long-wet season (10.53%) (p = 0.034). Phylogenetic analysis of the sequenced samples revealed that the detected HEV strains are closely related to Orthohepevirus C genotype C1 previously associated with rodents rather than to the classical human HEV genotypes. This finding raises important questions about possible zoonotic transmission in densely populated urban areas. Conclusion This is the first study to report HEV detection and genetic analysis in wastewater from the Mfoundi Division of Yaoundé, and only the second such report in Cameroon. The presence of HEV in community wastewater, especially from residential and irrigation sites, suggests widespread circulation and potential environmental and foodborne risks. The identification of HEV-C1-like strains highlights the possible role of rodents in transmission. These findings emphasize the importance of integrating wastewater surveillance into public health strategies and call for further research on zoonotic sources through a One Health lens.